Learning in the oviposition preference of Chilo partellus - Har, Nirmal S Hari; Jindal, Jawala; Aggarwa, Naveen l (Indian Journal of Plant Protection, 2020)
Learning may change the host selection behaviour of ovipositing females and certainly this phenomenon has implications on the success of trap cropping in agro ecosystems. Here, we have taken maize (Zea mays L.) - Napier millet (Pennisetum purpureum Schmach. Ã— P. glaucum L.) trap cropping system as model to assess if learning of crambid moth Chilo partellus (Swinhoe) could affect the subsequent oviposition preference on these host plants. Post-alighting host selection in ovipositing moths was assessed using modified tethered technique. In laboratory cages, previous experience with a host plant did not affect the oviposition preference of female moths. A strong oviposition preference was recorded for Napier millet in different treatment sets. However, when maize experienced moths were tested in field cages, both host plants were equally selected for oviposition. Whereas both naïve and Napier millet experienced moths preferred Napier millet to maize for oviposition in field cages. The exposure with either host did not alter the post-alighting host acceptance behaviour. The implications of these findings on the success of Napier millet as trap crop against C. partellus in maize-based cropping systems are discussed.